Development and validation of an LC–MS/MS method for simultaneously determining doxapram and keto-doxapram in human serum. (March 2017) - Suzuki, Yuki; Kamada, Noboru; Ohno, Hitoshi; Abe, Yoshikazu; Endo, Takuro; Kobayashi, Mamoru
Aim: Doxapram, a respiratory stimulant, is used to treat apnea. A reliable method of determining doxapram in blood is required for monitoring purposes.Results: Doxapram, keto-doxapram (active metabolite) and propranolol (internal standard) were extracted from human serum by protein precipitation and plate filtration. Molecular ions were generated by electrospray ionization in positive ion mode, and the ions were analyzed using a triple-quadrupole mass spectrometer. The calibration curves were linear from 20 to 5000 ng/ml. The method was validated and the selectivity, reproducibility and stability met the acceptance criteria.Conclusion: An LC–MS/MS method was successfully developed for determining doxapram and keto-doxapram in human serum. The method can be used to monitor doxapram and keto-doxapram concentrations in blood.